Dynamic range of camera in photography - Oon, Nicole Xin Jie (Nanyang Technological University, 2019)
When taking photographs with a digital camera under bright sunshine, it is often the case that we lose details of the image due to over exposure in areas where it is too bright showing only pure white colour and under exposure in area where it is too dark showing only pure black colour. This is due to the dynamic range of the camera resulting in a difference in the image captured and what the human eye sees. Dynamic range is a measure of the ratio of the maximum and minimum measurable light intensity, which is also the total amount of light captured in a scene. Unlike the camera, the human eye has a higher dynamic range which allows the human eye to see in a wider range of light intensities. This project will plan to investigate the dynamic range of camera in photography as well as exploring potential methodologies to retain as much details of the image as possible under circumstances of over or under exposure. Matlab will be used to for to first find trends in difference in exposure settings during photography. Thereafter, Matlab is used to test for improvement methods based on trends discovered previously and from theories – histogram equalization & log transformation Trend results shows that the relationship between pre HDR processed and post HDR processed images is a logarithmic graph. Due to various reasons affecting the output image, layering of modified algorithms from present theories has to be applied to images to achieve detail preserving images. Further works in terms on hardware can be further improved.